Nano-size Polymers Preparation, Properties, Applications - Fakirov, Stoyko; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book details all current techniques for converting bulk polymers into nano-size materials. The authors highlight various physical and chemical approaches for preparation of nano-size polymers. They describe the properties of these materials and their extensive potential commercial applications.
Part 1. Introduction -- Nano-Polymer Materials: How to Generate Them and Do We Need Them? -- Part 2. Chemical Approaches for Preparation of Nano-Size Polymers -- Nanosized Polymer Structures via Self-Assembly and Co-Assembly Approaches -- Direct Synthesis of Nano-size Polymers by Microemulsion Polymerization -- Part 3. Physical Approaches for Preparation of Nano-Size Polymers -- Electrospinning: Current Status and Future Trends -- Synthesis and Properties of Cellulose Nanowhiskers and Their Nanocomposites -- From Polymer Blends to Nano-Size Materials with Controlled Nanomorphology -- Electrospun Polymer Nanofiber Separators and Electrolyte Membranes for Energy Storage and Conversion Applications -- Converting of Bulk Polymers into Nanofibrils via Hot Stretching of Polymer Blends -- Nano-Size Polymers via Precipitation of Polymer Solutions -- Fabrication and Properties of Spin-Coated Polymer Films -- Part 4. Application Opportunities of Nano-Size Polymers -- Electrospinning- Commercial Applications, Challenges and Opportunities -- Nanofibrillar Single Polymer Composites: Preparation and Mechanical Properties -- Template-Assisted Approaches for Preparation of Nanosized Polymer Structures.
Keywords: Nanotechnology; Polymers; Microtechnology; Microelectromechanical systems; Chemistry, Technical; Nanotechnology; Polymers; Microsystems and MEMS; Industrial Chemistry